2021
DOI: 10.1016/j.intimp.2021.107567
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of SARS-CoV-2 spike protein-interacting cells in human tissues

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic. However, the mechanism of tissue tropism of SARS-CoV-2 remains unclear. Here, recombinant receptor-binding subdomain 1 of spike protein of SARS-CoV-2 (RBD-SD1) was used as a probe to investigate the potential tropism of SARS-CoV-2 in thirty-three types of normal human tissues. RBD-SD1 probe was observed to interact with cells in reported SARS-CoV-2 infected organs. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Importantly, previous studies have shown that COVID-19 can significantly affect the hematological and immunological systems, resulting in lymphopenia, thrombocytopenia, immature/dysfunctional neutrophil accumulation, etc., suggesting dysregulated hematopoiesis in the BM of COVID-19 patients. Using RBD subdomain 1 of the spike protein of SARS-CoV-2 (RBD-SD1) as a probe to investigate the potential tropism of SARS-CoV-2 in 33 types of normal human tissue, RBD-SD1 has been found to strongly interact with BM cells [ 145 ]. We recently conducted a scRNA-seq analysis (Wang et al, Cell Discovery, accepted) to characterize the BM mononuclear cell atlas in COVID-19 patients.…”
Section: Immune Landscape Of Covid-19mentioning
confidence: 99%
“…Importantly, previous studies have shown that COVID-19 can significantly affect the hematological and immunological systems, resulting in lymphopenia, thrombocytopenia, immature/dysfunctional neutrophil accumulation, etc., suggesting dysregulated hematopoiesis in the BM of COVID-19 patients. Using RBD subdomain 1 of the spike protein of SARS-CoV-2 (RBD-SD1) as a probe to investigate the potential tropism of SARS-CoV-2 in 33 types of normal human tissue, RBD-SD1 has been found to strongly interact with BM cells [ 145 ]. We recently conducted a scRNA-seq analysis (Wang et al, Cell Discovery, accepted) to characterize the BM mononuclear cell atlas in COVID-19 patients.…”
Section: Immune Landscape Of Covid-19mentioning
confidence: 99%
“…Peripheral immune cells are derived from hematopoietic stem and progenitor cells (HSPCs) in bone marrow (BM) 25 . In a recent report, recombinant receptor-binding subdomain 1 of spike protein of SARS-CoV-2 (RBD-SD1) was used as probe to study the potential tropism of SARS-CoV-2 in 33 types of normal human tissues, and the results showed that over 80% of RBD-SD1 probe strongly interacted with BM cells 26 , suggesting the importance of understanding how COVID-19 affects the BM niche, especially the hematopoietic stem cell (HSC) 27 .…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 was reported to invade various tissues such as the lung, nerve, adrenal, esophagus, thymus, pancreas, breast, skin cervix, and lymph node ( 22 ), with different susceptibility across these tissues ( 22 , 23 ). In this study, we analyzed the expression profiles of SARS-CoV-2-required genes in normal tissue types and explored whether this might influence the susceptibility of the corresponding tissue tumor to SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%